Treatment With an Angiopoietin-1 Mimetic Peptide Improves Cognitive Outcome in Rats With Vascular Dementia - Culmone, Lauren; Powell, Brianna; Landschoot-Ward, Julie; Zacharek, Alex; Gao, Huanjia; Findeis, Elizabeth L.; Malik, Ayesha; Lu, Mei; Chopp, Michael; Venkat, Poornima (Frontiers in Cellular Neuroscience, 2022)
Background and Purpose Vascular dementia (VaD) is a complex neurodegenerative disease affecting cognition and memory. There is a lack of approved pharmacological treatments specifically for VaD. In this study, we investigate the therapeutic effects of AV-001, a Tie2 receptor agonist, in middle-aged rats subjected to a multiple microinfarct (MMI) model of VaD. Methods Male, 10–12 month-old, Wistar rats were employed. The following experimental groups were used: Sham, MMI, MMI+1 μg/Kg AV-001, MMI+3 μg/Kg AV-001, MMI+6 μg/Kg AV-001. AV-001 treatment was initiated at 1 day after MMI and administered once daily via intraperitoneal injection. An investigator blinded to the experimental groups conducted a battery of neuro-cognitive tests including modified neurological severity score (mNSS) test, novel object recognition test, novel odor recognition test, three chamber social interaction test, and Morris water maze test. Rats were sacrificed at 6 weeks after MMI. Results There was no mortality observed after 1, 3, or 6 μg/Kg AV-001 treatment in middle-aged rats subjected to MMI. AV-001 treatment (1, 3, or 6 μg/Kg) does not significantly alter blood pressure or heart rate at 6 weeks after MMI compared to baseline values or the MMI control group. Treatment of MMI with 1 or 3 μg/Kg AV-001 treatment does not significantly alter body weight compared to Sham or MMI control group. While 6 μg/Kg AV-001 treated group exhibit significantly lower body weight compared to Sham and MMI control group, the weight loss is evident starting at 1 day after MMI when treatment was initiated and is not significantly different compared to its baseline values at day 0 or day 1 after MMI. AV-001 treatment significantly decreases serum alanine aminotransferase, serum creatinine, and serum troponin I levels compared to the MMI control group; however, all values are within normal range. MMI induces mild neurological deficits in middle-aged rats indicated by low mNSS scores (<6 on a scale of 0–18). Compared to control MMI group, 1 μg/Kg AV-001 treatment group did not exhibit significantly different mNSS scores, while 3 and 6 μg/Kg AV-001 treatment induced significantly worse mNSS scores on days 21–42 and 14–42 after MMI, respectively. MMI in middle-aged rats induces significant cognitive impairment including short-term memory loss, long-term memory loss, reduced preference for social novelty and impaired spatial learning and memory compared to sham control rats. Rats treated with 1 μg/Kg AV-001 exhibit significantly improved short-term and long-term memory, increased preference for social novelty, and improved spatial learning and memory compared to MMI rats. Treatment with 3 μg/Kg AV-001 improves short-term memory and preference for social novelty but does not improve long-term memory or spatial learning and memory compared to MMI rats. Treatment with 6 μg/Kg AV-001 improves only long-term memory compared to MMI rats. Thus, 1 μg/Kg AV-001 treatment was selected as an optimal dose. Treatment of middle-aged rats subjected to MMI with 1 μg/Kg AV-001 significantly increases axon density, myelin density and myelin thickness in the corpus callosum, as well as increases synaptic protein expression, neuronal branching and dendritic spine density in the cortex, oligodendrocytes and oligodendrocyte progenitor cell number in the cortex and striatum and promotes neurogenesis in the subventricular zone compared to control MMI rats. Conclusions In this study, we present AV-001 as a novel therapeutic agent to improve cognitive function and reduce white matter injury in middle aged-rats subjected to a MMI model of VaD. Treatment of MMI with 1 μg/Kg AV-001 significantly improves cognitive function, and increases axon density, remyelination and neuroplasticity in the brain of middle-aged rats.